Tin oxide nanoparticle formation using a surface modifying agent - Santos, LRB; Chartier, T.; Pagnoux, C.; Baumard, J. F.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Larbot, A. (Elsevier B.V., 2004)
This work presents results concerning the preparation of redispersible tin oxide nanoparticles achieved by using Tiron molecule ((OH)(2)C(6)H(2) (SO(3)Na)(2)) as surface modifying agent. The adsorption isotherm measurements show that an amount of 10 wt.% of Tiron is need to recover the SnO(2) nanoparticles surface with a monolayer. These nanoparticles can be easily redispersed in tetramethyl ammonium hydroxide at pH greater than or equal to11 until a powder concentration of 12 vol.% of tin. Under these conditions, hydrodynamic particle size is about 7 nm and increases until 52 nm at pH 6 due to the aggregation phenomenon. The time evolution of the viscoelastic properties indicates that the suspensions at pH 12.5, containing 12 vol.% tin oxide and 10 wt.% of surface modifier are kinetically stable. After thermal treatment at different temperature the powder characterisation evidences that the presence of Tiron monolayer at the nanoparticles surface increases the thermal stability of the porous texture and prevent the micropore size growth. This set of results contributes to satisfy the demand for more controlled synthesis of nanoparticles with high thermal stability as required for fabrication of ultrafiltration ceramic membranes. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: membranes; sol-gel processes; SnO(2); powders; chemical preparation